Infant-mother attachment in an urban poor sample - Guiang, Rowena S. (2005)
This exploratory study of attachment in an urban poor sample in Tacloban City sought to investigate the participants' conceptualization of attachment, the antecedents of attachment and to describe these behaviors. Using naturalistic observations, ten mother-infant dyads drawn from an urban poor sample were observed in their homes for a period of 5 months. This was supplemented by interviews with the mothers and alternative caregivers at the end of the 5 months of observations. The coding of these observations and interviews indicate that urban poor mothers viewed attachment in terms of infant care and emphasized proximity seeking and maintaining behaviors in infants. It also yielded the following attachment behaviors as well as maternal variables related to attachment: proximity seeking, separation distress, wariness of strangers, reunion behaviors, mother-infant interaction, maternal availability, appropriateness of stimulation, and maternal responsiveness. These attachment behaviors were directed differentially and more frequently towards attachment figures. Infants were clearly attached by the end of the first year of life to their mothers as well as to other people."
Keywords: Mother and infant